Pemenuhan Asas Keadilan Dalam Penyelesaian Kasus Tindak Pidana Kecelakaan Lalu Lintas Melalui Restorative Justice di Kejaksaan Negeri Sragen: Studi Kasus Perkara Nomor: PDM-12/SRGN/EKU.2/03.2023 - Charlissa Aulia Diva Febrianna; Anita Zulfiani (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
The criminal system in Indonesia is experiencing reform, which is marked by restorative justice. The principle of restorative justice is a principle of law enforcement in resolving cases which is used as an instrument for the recovery process from its original state. This is done to prevent problems from arising such as the number of prisoners in prison being full. Therefore, this legal research aims to analyze the fulfillment of the principles of justice in resolving traffic accident criminal cases through restorative justice at the Sragen District Prosecutor's Office and to analyze the obstacles faced by prosecutors in implementing restorative justice. This research uses a descriptive normative-empirical method with a legal approach and a traffic accident criminal case approach handled at the Sragen District Prosecutor's Office in case number: PDM-12/SRGN/EKU.2/03.2023. Based on this legal research, the author concludes that the resolution of traffic accident criminal cases through restorative justice at the Sragen District Prosecutor's Office has fulfilled the principles of justice as one of the legal objectives. However, in its implementation there are still obstacles experienced by the Prosecutor as a facilitator in this peace process.